Viral etiology and clinical characteristics of acute respiratory tract infections in hospitalized children in southern Germany (2014-2018) - Tabatabai, Julia; Ihling, Clara Marlene; Manuel, Britta; Rehbein, Rebecca M.; Schnee, Sarah Valerie; Hoos, Johannes; Pfeil, Johannes; Grulich-Henn, Jürgen; Schnitzler, Paul (Open Forum Infectious Diseases, 2023)
Viral acute respiratory tract infections (ARTIs) are a leading cause of hospitalization in infants and young children.During the winter seasons of 2014-2018, hospitalized children (<18 years) with symptoms of ARTI were prospectively included at the University Hospital Heidelberg, Germany. Nasopharyngeal swabs were obtained for multiplex molecular analysis of 10 groups of respiratory viruses, and clinical data were obtained using a standardized questionnaire.Of 1353 children included in this study, 1142 (84.4%) were positive for ≥1 viral pathogen. Virus monoinfection was detected in 797 (69.8%) children, whereas 345 (30.2%) children had coinfections with 2-4 viral pathogens. Respiratory syncytial virus (RSV), rhinovirus, and influenza virus were the main pathogens detected. RSV-positive children had significantly more often lower ARTIs, including symptoms of severe cough, wheezing, chest indrawing, tachypnea, and pulmonary rales. Hospitalized children aged <6 months represented the largest age group with detection of ≥1 viral pathogen (455/528 [86.2%] children). Coinfection was more frequent in younger children and, particularly for RSV with rhinovirus, significantly associated with more severe respiratory symptoms (P = .01).A better understanding of the etiology of viral ARTIs among hospitalized children plays a key role for future strategies in prevention, control, and treatment of respiratory viral infections.
Online veröffentlicht: 1. März 2023
Gesehen am 02.10.2023